Report on the first detection of Asian citrus psyllid Diaphorina citri Kuwayama (Hemiptera: Liviidae) in the Republic of Benin, West Africa - Mamoudou Sétamou; Yovanna L. Soto; Martine Tachin; Olufemi J. Alabi (Scientific Reports, 2023)
Abstract The Asian citrus psyllid (ACP), Diaphorina citri, was detected for the first time in the Republic of Benin, West Africa. The ACP is a known vector of Candidatus Liberibacter asiaticus (CLas), the putative causal agent of the devastating Huanglongbing (HLB; citrus greening disease). During visual surveys, ACP was only observed on residential citrus trees in southern Benin, but not in residential areas or commercial groves in the central and northern parts of the country. Its identity was confirmed morphologically and molecularly via DNA barcoding with published primers. Analysis of the obtained sequences showed that the ACP recorded in Benin clustered with the ones previously reported from Nigeria, suggesting a common origin of both populations. The ACP samples from Benin also carried Ca. Carsonella ruddii and Ca. Profftella armatura, two commonly found ACP endosymbionts. However, all the sampled ACP individuals tested negative for Ca. Liberibacter africanus, Ca. Liberibacter americanus, and CLas by quantitative polymerase chain reaction. This is the second report of the ACP in West Africa after Nigeria, the eastern bordering country of the Republic of Benin. Benin has an expanding commercial citrus industry, especially in the southern part of the country. Although the ACP samples tested negative for the HLB associated bacteria, the detection of ACP in the country requires swift actions including area-wide surveys to determine the extent of spread of this pest and the implementation of eradication or control efforts to prevent its establishment and spread of HLB in the country.